2022
DOI: 10.1186/s12884-022-04955-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing exclusive breastfeeding practice among under-six months infants in Ethiopia

Abstract: Background World Health Organization recommends exclusive breastfeeding (EBF) for the first 6 months of life. EBF has sustainable long-term health benefits for both infants and mothers. Despite its benefits, the practice of EBF in Ethiopia is lower than the internationally recommended one. This study aimed at identifying factors influencing EBF practice among under-6 month infants in Ethiopia. Methods This study used data drawn from the 2019 Ethiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 59 publications
1
11
0
2
Order By: Relevance
“…However, this study had limitations in that the EMDHS is mostly based on respondents' self-report and might have the possibility of recall bias. In addition, some variables like weight of child at birth [ 47 , 53 , 54 ], maternal anemia [ [54] , [55] , [56] ], child's breastfeeding status [ 7 , 47 , 57 ], diarrhea [ 48 , 58 , 59 ], pregnancy desire [ 60 , 61 ], mother's employment status [ 48 , 62 , 63 ] and fathers' educational status [ 64 , 65 ] were not included in the study because of large number of missing values/unavailability in the dataset.…”
Section: Strength and Limitations Of The Studymentioning
confidence: 99%
“…However, this study had limitations in that the EMDHS is mostly based on respondents' self-report and might have the possibility of recall bias. In addition, some variables like weight of child at birth [ 47 , 53 , 54 ], maternal anemia [ [54] , [55] , [56] ], child's breastfeeding status [ 7 , 47 , 57 ], diarrhea [ 48 , 58 , 59 ], pregnancy desire [ 60 , 61 ], mother's employment status [ 48 , 62 , 63 ] and fathers' educational status [ 64 , 65 ] were not included in the study because of large number of missing values/unavailability in the dataset.…”
Section: Strength and Limitations Of The Studymentioning
confidence: 99%
“…Exclusive breastfeeding practice among under-6-month infants was significantly associated with place of residence, maternal educational level, ANC visits, family size, mode of delivery, and place of delivery [19]. The findings of this study, the age of the mother at the time of having an infant is related to the practice of IYCF.…”
Section: Discussionmentioning
confidence: 55%
“…There hasn't been much progress, despite Ethiopia's government's best efforts to encourage and enforce exclusive breastfeeding for babies under six months of age the Ethiopian national gure shows that it has only 1% increase from 2016 (58%) to 2019 (59%) (12). This could be due to various contributing characteristics which may be related with infant, mother's socio-economic, demographic, obstetric and health care factors related to infant and mother such as: age of infant, sex of child, birth order, time of initiation, birth interval, age of mother, sex of head of the household, marital status, maternal educational level religion, household wealth index, family size, counseling service, type of birth, antenatal care (ANC), postnatal care (PNC), place of delivery, mode of delivery, and place of residence (3,4,11,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies indicated various factors that could signi cantly in uence EBF practices. A study conducted in Ethiopia showed that the female infants (22), infant aged 0-1month and 2-3 months (16, 25), being a single birth (16), breastfeeding initiation within one hour of birth (16, 17), mothers having secondary and higher education (19,20,23), women age 25-34 years (20), married mothers (18, 20), richer household wealth index (21,22,25), mothers having ANC visits (16,18,19,21,22,26,27), postnatal care checkup (13,16,18,21,23,26), deliveries at health facilities (13,19,20,23,26,28) receive breastfeeding counseling (17,18,25,27,28), urban residence (20) were positively associated with EBF practice among under-6 month infants. In contrary studies conducted in Ethiopia showed that the children aged 4-5 months (15), urban residences (19,26), women age 35-49 years (24), family size of more than 5 (19,20), caesarean births (15,19,21), richer household wealth status (14,20), residing in Afar region (15), and residing in Somali regi...…”
Section: Introductionmentioning
confidence: 99%